The diversity in nutritional profile of farmed edible bird’s nests from several regions in Indonesia - Lina Elfita; IETJE WIENTARSIH; DONDIN SAJUTHI; INDRA BACHTIAR; HUDA SHALAHUDIN DARUSMAN (Society for Indonesian Biodiversity, 2020)
Abstract. Elfita L, Wientarsih I, Sajuthi D, Bachtiar I, Darusman HS. 2020. The diversity in nutritional profile of farmed edible bird’s nests from several regions in Indonesia. Biodiversitas 21: 2362-2368.  Edible bird’s nest (EBN) is produced by certain swiftlet species mainly Aerodramus fuciphagus. This study aimed to compare the composition of proximate, nitrite, nitrate, amino acid and protein profiles of EBNs collected from different regions in Indonesia (West Sumatra, South Sumatra, West Java, West Kalimantan, Central Sulawesi, and Southeast Sulawesi). The results showed that the order of proximate composition was protein (53.09-56.25%) > carbohydrate (19.57-23.04%) > moisture (17.08-21.50%) > ash (5.44-6.25%) > fat (0.07-0.57%). Nitrite and nitrate contents were 3.11-18.28 ppm and 650.11-1051.06 ppm, respectively. Amino acid analysis found that EBNs contained 18 amino acids, composed of ten essential amino acids and eight non-essential amino acids. Aspartic acid content of EBNs from West Sumatra and West Kalimantan (4.21 and 3.27%, respectively) were much higher than the one found in other regions, which was on the range of 0.32-0.37%. SDS-PAGE analysis demonstrated that majority of EBNs possessed seven protein bands with molecular weight range of 19.6 to 82.7 kDa. However, EBNs from West Sumatra and West Kalimantan showed abundant of protein with molecular weight of approximately 34.0 kDa. Thus, EBNs collected from different regions in Indonesia showed different nutritional profiles.